2005
DOI: 10.1017/s0263034605050627
|View full text |Cite
|
Sign up to set email alerts
|

Difference between relativistic petawatt-picosecond laser-plasma interaction and subrelativistic plasma-block generation

Abstract: Some preliminary views are presented to the topic "Fast High Density Plasma Blocks Driven by Picosecond Terawatt Lasers" of the UWS-International Workshop 1-4 December 2004 in Sydney, Australia, underlining the motivation to explain the difference between the relativistic and the subrelativistic effects of ps-laser pulse interaction with plasma at powers above TW. This refers to specifically selected experimental and theoretical presentations at the workshop containing results for explaining the differences bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The fact that highly ionized plasmas without any molecules with surface tension was derived from the electric fields within the Debye length at a plasma surface due to the gradient of the electrostatic energy density~Hora et al., 1984;Hora, 1991a!. The physics of Debye length for laser produced plasmas received a special development for the conditions of relativistic interaction for the proton beam generatioñ Hora, 2005b;Schaumann et al, 2005!, in …”
Section: Surface Energy and Quark-gluon Plasmamentioning
confidence: 99%
“…The fact that highly ionized plasmas without any molecules with surface tension was derived from the electric fields within the Debye length at a plasma surface due to the gradient of the electrostatic energy density~Hora et al., 1984;Hora, 1991a!. The physics of Debye length for laser produced plasmas received a special development for the conditions of relativistic interaction for the proton beam generatioñ Hora, 2005b;Schaumann et al, 2005!, in …”
Section: Surface Energy and Quark-gluon Plasmamentioning
confidence: 99%
“…Further, the introduction of ultra high power laser [16] has led to many theoretical and experimental studies in the inertial confinement fusion (ICF) [17][18][19][20], charged particle acceleration [21][22][23] and ionospheric modification [24][25][26][27]. In many of such studies the ponderomotive as well as the relativistic nonlinearities have to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…(4) and (27) with separate variation of parameters representing the collisional frequency, initial irradiation intensity and electron temperature, initial laser beam-width, where parameters a ¼ 0.2404, b ¼ 1, c ¼ 0.2, and q 2 0 ¼ 100 in Fig. 7 are chosen as a contrast.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] For efficient interactions with plasmas, laser beams should be required to preserve strong intensity and propagate several Rayleigh lengths; hence, the main thrust of experimental and theoretical studies on propagation characteristics of laser beams has been directed toward the self-focusing and irradiation attenuation. In experiments, it has been confirmed that intense short laser pulses could propagate quite long distances with nonlinear self-focusing offsetting the diffraction divergence, [10][11][12] which evokes the upsurge in theoretical studies of nonlinear mechanisms.…”
Section: Introductionmentioning
confidence: 99%